2019
DOI: 10.1155/2019/8413698
|View full text |Cite
|
Sign up to set email alerts
|

Recent Potential Noninvasive Biomarkers in Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a rare but devastating gastrointestinal disease that predominately affects preterm neonates. Numerous studies have revealed that NEC is strongly associated with very low birth weight, degree of prematurity, formula feeding, infection, hypoxic/ischemic injury, and enteric dysbiosis. Given these clinical associations, the search for a deeper understanding of disease pathogenesis has led to an intense interest in the discovery and development of noninvasive biomarkers of NEC fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
(63 reference statements)
0
15
0
2
Order By: Relevance
“…Existing evidence supports a dominant role for microbial dysbiosis in NEC pathogenesis (18,19,21,(30)(31)(32), while experimental studies showed that germ-free animals do not develop NEC (26). Clinical studies demonstrated significant differences in gut microbiota composition between low birth weight and normal birth weight infants as well as between infants with and without NEC (33,34). Moreover, a systematic review suggested that alterations in intestinal microbiota by means of decreased firmicutes and Bacteroidetes and increased proteobacteria precede the onset of NEC (35).…”
Section: Pathophysiology and Current Diagnosis Of Necrotizing Enterocmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence supports a dominant role for microbial dysbiosis in NEC pathogenesis (18,19,21,(30)(31)(32), while experimental studies showed that germ-free animals do not develop NEC (26). Clinical studies demonstrated significant differences in gut microbiota composition between low birth weight and normal birth weight infants as well as between infants with and without NEC (33,34). Moreover, a systematic review suggested that alterations in intestinal microbiota by means of decreased firmicutes and Bacteroidetes and increased proteobacteria precede the onset of NEC (35).…”
Section: Pathophysiology and Current Diagnosis Of Necrotizing Enterocmentioning
confidence: 99%
“…Excellent review articles on conventional and emerging biomarkers for NEC diagnosis that have been published are recommended for readers interested in more details (34,60,62,74).…”
Section: Most Promising Biomarkers For Necmentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC) is a rare but devastating GI disease that predominately affects preterm neonates [ 108 ]. The pathogenesis of NEC is incompletely understood and appears to be multifactorial.…”
Section: Necroptosis and Intestinal Diseasesmentioning
confidence: 99%
“…Necrotizing enterocolitis (NEC) is a rare but devastating gastrointestinal disease that predominately affects preterm neonates [103]. The pathogenesis of NEC is incompletely understood and appears to be multifactorial.…”
Section: Necrotizing Enterocolitis (Nec)mentioning
confidence: 99%